Răspuns :
a) 6 cm
=> A = l (la puterea a 2 a) = 6 ( la puterea a 2 a) = 6 × 6 = 36 cm
b) 1,5 cm
=> A = l ( la puterea a 2 a ) = 1,5 ( la puterea a 2 a) = 1,5 × 1,5 = 2,5 cm
c) A = l ( la puterea a 2 a) = 0,5 ( la puterea a 2 a) = 0,5 × 0,5 = 0,25
*Poza este tot de la raspunsul meu , pe un cont vechi *
* Sper ca te-am ajutat*
=> A = l (la puterea a 2 a) = 6 ( la puterea a 2 a) = 6 × 6 = 36 cm
b) 1,5 cm
=> A = l ( la puterea a 2 a ) = 1,5 ( la puterea a 2 a) = 1,5 × 1,5 = 2,5 cm
c) A = l ( la puterea a 2 a) = 0,5 ( la puterea a 2 a) = 0,5 × 0,5 = 0,25
*Poza este tot de la raspunsul meu , pe un cont vechi *
* Sper ca te-am ajutat*
![Vezi imaginea Denisaaaaaaaa1111](https://ro-static.z-dn.net/files/d0a/2b20877521c3eabf2b09d4652bd5b9d3.jpg)